THU0643-HPR PHYSIOTHERAPISTS' ADHERENCE TO OSTEOARTHRITIS CLINICAL GUIDELINES: A NATIONAL ITALIAN SURVEY. (2nd June 2020) - Battista, S.; Stefano, S.; Serena, M.; Testa, M.; Dell'isola, A.
Abstract : Background: Osteoarthritis (OA) is the most prevalent joint disease in the world, and one of the top causes of disability [1]. OARSI and EULAR guidelines recommend non-surgical interventions as first-line interventions for OA [2]. Despite this, only less than 40% of people suffering from OA receive the recommended intervention [3]. Objectives: The aim of this study is to investigate to what extent a population of Italian physiotherapists adhere to the OA-guidelines in their clinical practice. Methods: A quantitative web-based cross-sectional survey was developed according to the Checklist for Reporting Results of Internet E-Survey. The questionnaire was realised in Italy by a panel of physiotherapists, based on the EULAR, OARSI and NICE OA-guidelines. The questionnaire was delivered using REDCap through the Italian Association of Physiotherapists and the University of Genoa newsletters. The questionnaire was divided into two sections. The first section included 24 statements adapted from the aforementioned guidelines. Participants were asked to express their statement agreement on a scale from 1 (completely disagree) to 5 (completely agree). Participants who partially or totally agreed (score 4-5) were considered to agree with the statements. We defined a ≥ 70% agreement with a statement as consensus. In the second section, a clinical vignette was presented, illustrating an OA clinical case. Participants had to select, from a list of clinical options, how they would manage this case. Participants were classified as 'Delivering', 'Partially delivering' and 'Non-delivering' the recommended intervention, depending on the recommended or not-recommended interventions chosen. Results: 812 physiotherapists (age: 36±13, 59; 48% women) completed the survey between 26 November 2019 and 9 January 2020. The consensus was achieved for 12 sentences (52%) out of 23 (Fig. 1 ). All the statements focussed on exercise, education, and surgical referral received > 70% of agreement, whereas no consensus was reached for the statements on the clinical diagnostic criteria, for the use of glucosamine or chondroitin products and for the use of topic NSAIDs. In the second section, 20% of the analysed physiotherapists would deliver an intervention in line with OA guidelines and a 20% would carry out an intervention that is partially in line with OA guidelines. Conversely, the 40% of the participants of this survey would include at least a not-recommended intervention, considered, therefore, as 'non-delivering' the recommended intervention (Fig. 2 ). Conclusion: Our findings reveal an overall sub-optimal adherence to OA-guidelines in a sample of Italian physiotherapists. Italian physiotherapists appear to be aware of the importance of exercise and education for patients suffering from OA. Instead, a sub-optimal level of knowledge was found regarding the criteria for OA clinical diagnosis and on the role of other non-surgical interventions in the management of OA. These results identified some gaps between evidence and clinical practice, which may lead to an incorrect management of patients suffering from OA. References: [1]GBD 2017 Collaborators. Global, regional, and national incidence, prevalence, and years lived with disability for 354 diseases and injuries for 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017. Lancet . 2018;392:1789–858. [2]Fernandes, L. et al. EULAR recommendations for the non-pharmacological core management of hip and knee osteoarthritis. Ann Rheum Dis . 2013;72:1125–35. [3]Basedow M et al. Assessing appropriateness of osteoarthritis care using quality indicators: a systematic review. J Eval Clin Pract . 2015;21:782–9. Disclosure of Interests: None declared